2016
DOI: 10.1590/1413-785220162403157540
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Injury in Childhood: What Is Its Current Importance?

Abstract: Objective: The purpose of this study was to assess the importance of pelvic fractures in childhood by analyzing epidemiological characteristics and associated injuries.Methods: This is a retrospective study performed between 2002 and 2012 at two trauma referral centers in São Paulo. We identified 25 patients aged 16 years old or younger with pelvic fracture.Results: The main mechanism of trauma was traffic accident (80%), followed by fall from height (16%). At hospital admission, 92% had traumatic brain injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…However, it did not consider the bony pelvis’ changing maturity throughout the children’s age range. In our cohort, Torode type III was the most common pelvic ring injury (68.3%) which is similar to what has been reported previously [ 6 , 8 , 18 ]. On the other hand, Niedzielki et al [ 21 ] reported that the frequent type of fracture among children is avulsion fractures secondary to sports injuries.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, it did not consider the bony pelvis’ changing maturity throughout the children’s age range. In our cohort, Torode type III was the most common pelvic ring injury (68.3%) which is similar to what has been reported previously [ 6 , 8 , 18 ]. On the other hand, Niedzielki et al [ 21 ] reported that the frequent type of fracture among children is avulsion fractures secondary to sports injuries.…”
Section: Discussionsupporting
confidence: 91%
“…High-energy blunt trauma is the leading mechanism of pediatric pelvic fractures primarily due to motor vehicle accidents and fall from height [2][3][4]. Pelvic fracture in pediatric population is a marker of the injury severity which showed association with injuries to the head and intra-abdominal region and greater risk of hemorrhage [2,8,9]. Hemorrhage as reported in adult pelvic fractures that leads to hemodynamic instability is rarely observed in pediatric pelvic fracture [2,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…129 Extra-pelvic injuries While rare, the urogenital system can be injured anywhere from the kidneys to the urethral opening following blunt abdominal trauma. 133,134 Surgeons should be mindful of patients with MTZ III and above pelvic fractures who also present with haematuria, dysuria, urinary retention or incontinence. 134,135 Organs such as the kidney are relatively larger in the child, and the perirenal fat is not as well developed to cushion against injury.…”
Section: Pelvic and Functional Complicationsmentioning
confidence: 99%
“…그렇기 때문에 세심한 이학적 검사와 관찰, 그리고 방 사선 검사가 필요하다. 특히나 CT를 이용한 골절의 검사는 동반 된 골반과 복부 장기의 손상을 검사할 수 있을 뿐만 아니라 3차원적 영상으로 골절을 보다 쉽게 이해하게 도와준다 5,6).…”
unclassified